Effect of Capacity Development Program on Health Literacy to Prevent COVID-19 amongst Public Health Volunteers in Bangkok - Chansombut , Chotirot; Auemaneekul, Naruemon; Lagampan, Sunee (Journal of The Royal Thai Army Nurses, 2025)
Quasi-experimental research with a two-group pretest-posttest and follow-up design aimed at exploring the effects of a capacity development program on health literacy to prevent COVID-19 amongst public health volunteers in Bangkok. The sample group consisted of 40 public health volunteers in Bangkok. The study period was 4 weeks and followed up for 4 weeks. The experimental group received the program to develop cognitive skills, access skills, communication skills, media literacy skills, decision-making skills, and self-management skills. To promote health literacy and behavior to prevent COVID-19. Data were collected by answering questionnaires. Analyze the data as well. Frequency distribution, Average percentage, Standard Deviation, Chi-Square, Independent t-test, and Two-way Repeated Measures ANOVA. The research results found that after receiving the program, the health literacy and behaviors to prevent COVID-19 of the experimental group were better than before receiving the program and better than the control group to a statistically significant degree at p-value < .05. The results of this research are a guideline for developing the potential of public health volunteers in Bangkok. Control and prevention of the outbreak of COVID-19 and other infectious diseases. It is recommended that research on health literacy for public health volunteers in Bangkok be developed. In other matters such as chronic non-communicable diseases, cancer, and caring for dependent patients. To be consistent with current health problems.